PhoneGap 4 mobile application development cookbook : build real-world, hybrid mobile applications using the robust PhoneGap development platform /: build real-world, hybrid mobile applications using the robust PhoneGap development platform. (2015) - Pamungkas, Zainul Setyo; (Web application developer), Gifford, Matt
No abstract available